2010
DOI: 10.1111/j.1525-1446.2010.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Development ofMy Health Companion©to Enhance Self-Care Management of Chronic Health Conditions in Rural Dwellers

Abstract: Appropriate self-management support is needed to help individuals and their families meet the challenges of living with chronic health conditions. Such support is characterized by productive interactions between informed, active individuals and their health care providers. The purposes of this paper are to describe the challenges to achieving self-management support and a tool, My Health Companion© (MHC), which was developed to meet that challenge. The MHC is a paper personal health record designed to help rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…7,28-30 31 In remote areas, technology such as internet support groups, telehealth communication, and teaching models on disease states have been effective tools for improving health literacy, medication adherence, patient engagement and patient empowerment, especially for women. 7,12,23 Our study showed use of internet by respondents for preventative care and some future interest in using telehealth solutions for healthcare. For many rural areas, telehealth has been a great bridging opportunity to improve access and patient care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,28-30 31 In remote areas, technology such as internet support groups, telehealth communication, and teaching models on disease states have been effective tools for improving health literacy, medication adherence, patient engagement and patient empowerment, especially for women. 7,12,23 Our study showed use of internet by respondents for preventative care and some future interest in using telehealth solutions for healthcare. For many rural areas, telehealth has been a great bridging opportunity to improve access and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 By gaining a better understanding of rural cultural patterns of heath and health care through in-depth patient interviews, practitioners can develop patient-centered techniques to improve the health of rural communities.…”
Section: Innovations In Pharmacymentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21] Os dados que emergiram dos estudos analisados mostram que os rápidos avanços na tecnologia e acesso à internet tornaram-se não apenas um modo viável para a realização de intervenções educativas, mas também uma plataforma que pode ser divulgada e implementada amplamente. Além disso, as intervenções pela internet e os programas que podem ser por ela divulgados permitem que o conteúdo do programa possa ser padronizado, direcionado para idades específicas e fases do desenvolvimento e podem ser facilmente atualizados.…”
Section: Sujeitosunclassified
“…Esta foi uma estratégia desenvolvida pelo enfermeiro que contribuiu para o processo do autocuidado em saú-de, ocorrendo interações mais produtivas, uma vez que eles estão sujeitos a desenvolver doenças crônicas por muitas vezes não terem acesso imediato aos profissionais de saúde e de toda estrutura oferecida por cada esfera de atendimento para a promoção, prevenção e recuperação da saúde. 20,21 A partir do exposto, vale ressaltar que as pessoas que vivem na zona rural apresentam peculiaridades em seu modo de sobrevivência, pois desempenham atividades agrícolas, sobrevivendo de sua própria produção, com jornadas exaustivas de trabalho pesado e com a organização de hábitos e horários diferen- uma lacuna ao realizar a prática educativa a partir da utilização de folhas de orientações, pois cada pessoa tem o livre arbítrio em relação à sua vida. Cabe a ela a escolha de querer ou não fazer o uso das sugestões propostas ou parte delas e, também, utilizar suas próprias estratégias para lidar com os possíveis desconfortos que a doença proporciona.…”
Section: Sujeitosunclassified